Optimization of cabbage (Brassica oleracea var. capitata L.) protoplast transformation for genome editing using CRISPR/Cas9 - Stajič, Ester; Kunej, Urban (Frontiers in Plant Science, 2023)
Genome editing techniques, such as Clustered Regularly Interspaced Short Palindromic Repeats/CRISPR-associated systems (CRISPR/Cas9) are undoubtedly becoming an indispensable tool for improving food crops and tackling agricultural challenges. In the present study, key factors affecting transformation efficiency, such as PEG4000 concentration, incubation time, and plasmid amount were evaluated to achieve efficient delivery of CRISPR/Cas9 vector into cabbage protoplasts. Using amplicon sequencing, we confirmed a significant effect of PEG4000 concentration and incubation time on the induced target mutations. By optimizing the transformation protocol, editing efficiency of 26.4% was achieved with 40 µg of plasmid and 15 minutes incubation with 50% PEG4000. While these factors strongly affected the mutation rate, the viability of the transformed protoplasts remained high. Our findings would be useful for successful genome editing in cabbage and other brassicas, as well as in research areas such as gene function analysis and subcellular localization that rely on transient transformation methods in protoplasts.